THE STUDENT WHIT AUTISTIC SPECTRUM DISORDER (ASD) AND REMOTE LEARNING - Matoso dos Santos Telles, Livia Catarina; Florencio Fernandes Moret, Wrcia Cristina; Rodrigues Mendonca, Joao Guilherme [UNESP] (Univ Fed Sao Carlos, 2021)
This is qualitative research that investigated the pedagogical strategies adopted during the Covid-19 pandemic to assist a student with Autism Spectrum Disorder (ASD) enrolled at the Federal Institute of Rondonia (IFRO). ASD is a term that includes, among other manifestations, autism, and the individual usually presents deficits in communication, social and behavioral interaction at different levels. Thus, the objective was to understand how pedagogical strategies were planned and developed so that the autistic student could follow the classes at home, as well as having greater ease in interacting with classmates. The methodology involved accessing documents in digital media, without personal contact, during the period from June to November 2020. The results indicated that the Virtual Learning Environment (AVA) was adapted through an accessibility tab and monitoring through the remote inclusive monitoring, which is developed by a student under the supervision of a supervisor. Thus, the autistic student had weekly monitoring and support to overcome their learning difficulties, which were more accentuated in remote education.
Keywords: Autism; Remote education; Inclusive Monitoring Program